Analysis of working capital in relation with income of the small weaving industry in Kupang City - Wehelmina M. Ndoen (LPPM STIE KRAKATAU, 2025)
Purpose: This study aims to determine whether there is an effect of working capital on the income of the Small Weaving Industry in Kupang City. Research Methodology: This study used a survey with a quantitative descriptive approach. This research was conducted in the Small Weaving Industry in Kupang City with a total population of 49 weavers. The sample was taken using saturated samples. Methods of data collection using questionnaires, interviews, documentation and observation. The data analysis technique used is to use financial theory related to working capital and income. Results: The results showed that working capital has an effect on the income of small industrial weavers in Kupang City, because the greater the amount of working capital spent, the greater the income earned. Therefore, it is recommended that weavers keep working capital conditions so that the production process can be increased by itself the income will increase.